Odpowiedzi

Najlepsza Odpowiedź!
2010-03-02T22:38:27+01:00
2^-1 +3 ^-1)^-1= [(½)¹ + (⅓)¹]⁻¹ = [½+⅓] ⁻¹ = [³/₆ + ²/₆]⁻1 =
=(⁵/₆) ⁻¹ = (⁶/₅)¹ = ⁶/₅ = 1 ⅕

(-0,5)² - 0,3^-3 1^-5= 0,25 - (³/₁₀)⁻³ * (1)⁻⁵ = 0,25 - (¹⁰/₃)³ * 1 =
= 0,25 - ¹⁰⁰⁰/₂₇ = ¼ - 37 ¹/₂₇ = ²⁷/₁₀₈ - 37 ⁴/₁₀₈ = -36⁸⁵/₁₀₈

(⅘)^-1 + (-⁶⁴/₉)^-2 = (⁵/₄)¹ + (-⁹/₆₄)² = ⁵/₄ - ⁸¹/₄₀₉₆ =
= ⁵¹²⁰/₄₀₉₆- ⁸¹/₄₀₉₆ = ⁵⁰³⁹/₄₀₉₆ = 1 ⁹⁴³/₄₀₉₆

-(1/2)^-2 - (8/5)^-1 * (-8)
-------------------------------- <<<kreska ułamkowa
29^0 - 10^-2

-(2)² - (⁵/₈)¹ * (-8)
--------------------------------
1 - (¹/₁₀)²

-4 +5
-------------
1 - ¹/₁₀₀

1
----------------
¹ ⁰⁰/₁₀₀ - ¹/₁₀₀

1
---------
⁹⁹/₁₀₀

1 : ⁹⁹/₁₀₀ = 1 * ¹ ⁰⁰/₉₉ = ¹ ⁰⁰/₉₉ = 1 ¹/₉₉